Perceived barriers and facilitators to exercise in kidney transplant recipients: A qualitative study. (10th January 2022) - Billany, Roseanne E.; Smith, Alice C.; Stevinson, Clare; Clarke, Amy L.; Graham‐Brown, Matthew P. M.; Bishop, Nicolette C.
Abstract: Background: Exercise has the potential to attenuate the high levels of cardiovascular morbidity and mortality present in kidney transplant recipients (KTRs). Despite this, activity levels in KTRs remain low. The aim of this qualitative study was to explore the barriers and facilitators of exercise in KTRs. Methods: Thirteen KTRs (eight males; mean ± SD; age 53 ± 13 years; estimated glomerular filtration rate 53 ± 21 ml/min/1.73 m 2 ) were recruited and completed semistructured one‐to‐one interviews at University Hospitals of Leicester NHS Trust. All KTRs were eligible if their kidney transplant was completed >12 weeks before interview and their consultant considered them to have no major contraindications to exercise. All interviews were audio recorded, transcribed verbatim and subject to framework analysis to identify and report themes. Results: Themes were organized into personal, behavioural and environmental factors based on social cognitive theory. Facilitators of exercise were largely internal: enjoyment, exercise for general health and health of the transplanted kidney and desire to maintain normality. Social interaction, support and guidance of healthcare professionals and goal setting were perceived as motivational. Harming the kidney, a lack of guidance, self‐motivation and accessibility were barriers to exercise. Conclusion: These results provide detailed insight into the development of interventions designed to increase physical activity in KTRs. They provide strong evidence that specific exercise guidelines are required for this population and that the healthcare system could have a key role in supporting KTRs to become more physically active. Interventions need to be multifaceted to appeal to the differing levels of support desired by KTRs. Patient or Public Contribution: KTRs were involved in the development of the interview topic guide to ensure all relevant topics were explored.